Manager stimulation of employee self-regulated learning. Issue 5 (5th June 2017) - Lyons, Paul; Bandura, Randall P.
Abstract : Purpose: The purpose of this paper is to explore the potential benefits of integrating self-regulated learning with skill charting, a training and development tool. The following areas are examined: manager-as-coach, self-regulated learning, and skill development through skill charting. Design/methodology/approach: This discussion of manager stimulation through the integration of self-regulated learning and skill charting is based on an extensive literature review of recent research as well as that done by the authors. Findings: There are many practical opportunities for managers to enhance self-regulated learning of employees using skill charting. Because self-regulated learners tend to reflect a growth mindset they are more likely to engage in performance improvement, change and innovation. These personal characteristics are highly valued by most managers as they may provide a competitive advantage for organizations. Managers, acting as coaches with individuals or small groups, can be instrumental in helping employees to internalize self-regulating learning practices at the same time the employees participate in learning important job skills. The approach offered here also encourages team-building skills, knowledge acquisition, and employee engagement. Originality/value: This fresh look at an integration of self-regulated learning with the skill-charting approach offers specific, practical suggestions for manager stimulation of self-regulated learning.